Dispersion properties of electron acoustic waves in degenerate and non‐degenerate quantum plasmas. Issue 10 (12th August 2019) - Fahad, S.; Ahmad, Mushtaq; Jan, Qasim; Akram, F.
Abstract: The longitudinal response functions are used to generalize the dispersion properties of electron acoustic waves (EAWs) in the presence of quantum recoil, for isotropic, non‐relativistic, degenerate/non‐degenerate plasmas. In order to study the EAWs, the constituents of non‐degenerate (thermal) plasma are considered to be of two groups of electrons having different number density and temperature, namely the cold electrons and the hot electrons. Similarly in degenerate (Fermi) plasma the two population of electrons are considered to be the thinly populated and the thickly populated electrons. The sparsely populated electrons are termed as cold electrons while the densely populated ones are termed as hot electrons. The ions are stationary which form the neutralizing background. The absorption coefficients for Landau damping with the inclusion of the quantum recoil in both plasmas are calculated and discussed. The results are discussed in the context of laser‐produced plasma.